Ketertarikan Konsumen Melalui Testimoni dan Video Review di Media Sosial Instagram dan TikTok @adamasanya - Muhammad Riski Win Mario (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Online marketing via social networks has developed into an important communication system not only for producers of goods or services but for customers as well. The online shop that we often use and hear about is actually not something new. Online sales or e-commerce. The rise of online shops that have sprung up reflects the large number of people who are interested in shopping for second hand goods rather than buying new goods at online shops or directly at official shops to fulfill their needs and desires. The focus of the problem of this research is to explain how marketing communication strategies via Instagram social media are carried out at the Adamasanya online shop. Meanwhile, the aim of this research is to find out how marketing communication strategies via Instagram social media are carried out at the Adamasanya online shop. This research uses a qualitative approach, which is a type of field research, by analyzing online buying and selling practices carried out by Adamasanya on Instagram. Data collection techniques in this research were observation, interviews, literature study and documentation. The results of this research show that the communication process carried out by Adamasanya in marketing its products via the social media Instagram is by implementing a communication strategy that includes communication components (source, message, media, recipient, effect and feedback), as well as applying the 4P marketing principles ( product, price, place, promotion). In marketing communications, there are also supporting and inhibiting factors. The supporting factor is Instagram's various features which are very helpful in marketing. The inhibiting factor is the existence of other online business competitors who are increasingly interested. The effectiveness of marketing communications carried out by Adamasanya on Instagram has had a big influence.